Tackling mortality due to childhood tuberculosis - Godreuil, Sylvain; Marcy, Olivier; Wobudeya, Eric; Bonnet, Maryline; Solassol, Jérôme; Groc, Soraya; Abbate, Jessica L.; Le Gal, Frédéric; Gerber, Athenaïs; Tuaillon, Edouard (Lancet public health, 2018)
Day, an opportunity to promote greater commitment and leadership in the fight against tuberculosis at all levels. It is particularly urgent to increase awareness and mobilisation on childhood tuberculosis because tuberculosis mortality is still unacceptably high in children. Indeed, there were 253 000 deaths among one million estimated cases in 2016, almost exclusively in young children who did not receive treatment.1,2 Affordable and child-friendly treatments are available, but childhood tuberculosis is often underdiagnosed: only 45% of all estimated paediatric tuberculosis cases were notified to the WHO in 2016.1 This situation is partly explained by the lack of adapted health-care structures and the low implementation of public health policy and tools for the detection and prevention of childhood tuberculosis.
Keywords: mortality; childhood tuberculosis